IN SEARCH OF NEW OPPORTUNITIES: THE INDONESIANISASI OF ECONOMIC LIFE IN YOGYAKARTA IN THE 1950s - Purwanto, Bambang (Masyarakat Indonesia, 2013)
A flourishing study on Indonesia’s economic history in the last two decades has still been unable to change a general impression of limited role of the indigenous people in economic activities during modern times. The transformation of the Indonesian economy from a colonial economy to a national economy through the process of Indonesianisasi, went through different historical patterns. The independent Indonesia did not translate the idea of political nationalism directly into economic prosperity until the late 1950s. As a result, there is always only a small portion of independent entrepreneurs among the population, namely those who are supposed to run the public economy smoothly without political intervention. This paper provides theoretical considerations and historical facts on the process of Indonesianisasi. It discusses the economic life of people in Yogyakarta, the capital city Republic of Indonesia during the war of independence, soon after the recognition of Indonesia’s independence in December 1949.